ANALISIS RITUAL TRADISI NYADRAN SENDANG DI DUSUN SAWEN, KECAMATAN NGIMBANG , KABUPATEN LAMONGAN DALAM MENJAGA KELESTARIAN BUDAYA - Arinda Septarina Efendi; Qoni’ah Nur Wijayani (Journal of Student Research, 2024)
Indonesia is a country consisting of different races, ethnicities and religions. However, this does not become an obstacle to remaining tolerant and respectful of each other's culture. The culture in Indonesia has different characteristics and meanings in one region and another. Like the nyadran culture which is currently still highly respected in several areas, especially in the people of Sawen Hamlet, Ngimbang District, Lamongan Regency. This research aims to analyze the traditional culture of Nyadran Sendang which is still highly respected and preserved by the people of Sawen Hamlet, Ngimbang District, Lamongan Regency.